Raptivism on YouTube: Studying the Response of Videoart Prosumers to School Bullying in Spain - Ramírez-Hurtado, Carmen; Massó Guijarro, Belén (Pedagogika, 2023)
This study analyses the influence of the bullying prevention campaign „Se Buscan Valientes“ which, based on a song produced by a well-known rapper, invited schools throughout Spain to create videos and upload them to YouTube. We analysed the comment threads generated by the videos and conducted interviews with eight teachers who promoted participation in the campaign. The results reveal the beneficial effects of the arts as a tool to combat bullying.